Commissive Utterances In The Translation Of Islamic Holy Scripture Chapter Ash-Shu'ara (A Pragmatic Perspective) - Historiana, Dian Aulia (2016)
This research is aiming at 1) to find the intention of commissive utterances in the translation of Chapter Ash-Shu'ara and 2) to describe the politeness strategiesofcommissive utterances in the translation of Chapter Ash-Shu'ara. In this research, the researcher uses a descriptive qualitative as the type of the research. The data of this study areverses of Chapter Ash-Shu'ara containing commissive utterances.The researcher found five kinds of the intention of commisive utterances in the English translation Chapter Ash-Shu'ara based on Searle' classification. There are promising, threatening, refusing, vowing and volunteering. In addition, the researcher finds out other form of commissive utterance, it is challenging. The researcher found 8 verses of promising (24%), 8 verses of threatening (24%), 6 verses of refusing (18%), 2 verses of vowing (7%),5 verses of volunteering (15%) and 4 verses of challenging (12%).The majority of the intention of commissive utterances that the researcher found in English translation of Chapter Ash-Shu'ara is promising and threatening (24%). Then, researcher found four kinds of the politeness strategies, there are bald on record, positive politeness, negative politeness and off-record indirect strategies. The researcher found 15 verses using bald on record strategy (45%), 14 verses using positive politeness (42%), 1 verse using negative politeness (3%) and 3 verses using off-record indirect strategies (10%). The majority of politeness strategy that the researcher found is bald on record (45%). Keywords: commissive utterances, intention, politeness strategies